Effects of placebos without deception compared with no treatment: protocol for a systematic review and meta-analysis. Issue 11 (26th November 2015) - Petkovic, Grace; Charlesworth, James E G; Kelley, John; Miller, Franklin; Roberts, Nia; Howick, Jeremy
Abstract : Introduction: Placebos have long provided a robust control for evaluating active pharmacological preparations, but frequently demonstrate a variable therapeutic effect when delivered in double-blinded placebo-controlled trials. Delivery of placebos as treatment alone has been considered unethical, as it has been thought that deception is essential for their effect. However, recent evidence suggests that clinical benefit can be derived from placebos delivered without deception (unblinded/open-label) manner. Here, we present a protocol for the first systematic review and meta-analysis of studies of the effects of non-deceptive placebos compared with no treatment. Methods and analysis: This protocol will compare the effect of placebos delivered non-deceptively to no treatment. It will also assess the methods of delivery used for non-deceptive placebos. Studies will be sought through relevant database searches and will include those within disease settings and those among healthy controls. To be included, trials must include both non-deceptive (open-label) placebo and no treatment groups. All data extraction and analysis will be conducted by two independent reviewers. The analysis will evaluate any differences in outcome measures between the non-deceptive placebo and no treatment groups. Outcome measures will be the clinically-relevant outcomes detailed in the primary papers. The delivery methods, such as verbal instructions, which may provide positive expectations and outcomes, of non-deceptive placebos will also be assessed. Each study will be comprehensively assessed for bias. Subgroup analyses will identify any discrepancies among heterogeneous data. Ethics and dissemination: This review does not require ethical approval. The completed review will be widely disseminated by publication and social media where appropriate. This protocol has been registered on PROSPERO (2015:CRD42015023347).